2018
DOI: 10.3390/app8050660
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Patellar Tendon Abnormality in Asymptomatic Professional “Pallapugno” Players: A Texture-Based Ultrasound Approach

Abstract: Featured Application: Quantitative texture analysis of tendon ultrasound images for determination of subclinical tendinopathy.Abstract: Abnormalities in B-mode ultrasound images of the patellar tendon often take place in asymptomatic athletes but it is still not clear if these modifications forego or can predict the development of tendinopathy. Subclinical tendinopathy can be arbitrarily defined as either (1) the presence of light structural changes in B-mode ultrasound images in association with mild neovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…There are several ways including ultrasound and magnetic resonance imaging (MRI) to measure the tendon related with the patellar. Some previous studies have shown that ultrasound is an effective way to evaluate patellar tendonitis [11][12][13]. Measurement using ultrasound is inexpensive and can avoid radiation.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways including ultrasound and magnetic resonance imaging (MRI) to measure the tendon related with the patellar. Some previous studies have shown that ultrasound is an effective way to evaluate patellar tendonitis [11][12][13]. Measurement using ultrasound is inexpensive and can avoid radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound imaging is considered one of the most preferred methods for analyzing the morphological aspects of atherosclerotic plaque [3], [4], and can be chosen over CT and MRI as it is real-time, does not use ionizing radiation, and is inexpensive, while still allowing a morphological analysis of changes including ulceration, heterogeneity, and echogenicity in plaques [5]. However, processing ultrasound images is challenging due to poor resolution [6], the presence of manual markers and artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a search space of 50x4. The choice between the exploration and exploitation phases is controlled by a mathematical normalization function (NF) calculated from the search space, as shown in Eq (6)(7)…”
mentioning
confidence: 99%
“…Other methods in the literature have done research on other tendons rather than SST. In a similar research to [13], Meiburger et al [14] assessed the performance of 90 features, extracted from manually segmented regions, in a multivariate linear regression model for the patellar tendon abnormality detection. Their study showed that hand-crafted features can perform reasonably for tendon abnormality detection from US images.…”
Section: Introductionmentioning
confidence: 99%